2015
DOI: 10.1007/s11356-015-4455-1
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic immobilization in the contaminated soil using poorly crystalline Fe-oxyhydroxy sulfate

Abstract: A low crystalline Fe-oxyhydroxy sulfate (FeOS) was used to immobilize arsenic (As) in soils in this study. The effects of FeOS amount, treatment time and soil moisture on As immobilization were investigated. The results showed that water-soluble and NaHCO3-extractable As were immobilized by 53.4-99.8 and 13.8-73.3% respectively, with 1-10% of FeOS addition. The highest immobilization of water-soluble (98.5%) and NaHCO3-extractable arsenic (47.2%) was achieved under condition of 4% of FeOS and 80% of soil moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Nickel and zinc have an average immobilization of 96% and 99%, respectively (Table 11), which are fairly expected for these trace elements [45]. Arsenic has an immobilization rate, on average, of 99% indicating coprecipitation with secondary iron minerals [46]. Molybdenum (as molybdate) has, as expected, a lower immobilization rate at around 94%.…”
Section: Nisupporting
confidence: 70%
See 1 more Smart Citation
“…Nickel and zinc have an average immobilization of 96% and 99%, respectively (Table 11), which are fairly expected for these trace elements [45]. Arsenic has an immobilization rate, on average, of 99% indicating coprecipitation with secondary iron minerals [46]. Molybdenum (as molybdate) has, as expected, a lower immobilization rate at around 94%.…”
Section: Nisupporting
confidence: 70%
“…Specific immobilization mechanisms are hard to determine, but secondary immobilization takes place between the release from the waste and the sampling point in the surface waters. A major fraction of the release of trace elements is immobilized on surfaces close to the release through sorption, coprecipitation with iron oxyhydroxides and precipitation [45][46][47]. Immobilization in the pit lakes through sedimentation seems to be minor as the concentrations in the sediments are fairly low as indicated by the concentrations found in pit lake Norrtorpssjön (43 mg/kg dw As, 102 mg/kg dw Mo, 25 mg/kg dw Ni, 86 mg/kg dw U and 68 mg/kg dw V) [32].…”
Section: Trace Element/sulfate Ratiosmentioning
confidence: 99%
“…The characteristics of the soil samples were determined according to the previously described protocols . Briefly, soil pH was measured by a pH meter and the ratio of soil to water was 1:5 v / v .…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that iron has a strong affinity for arsenic and can be utilized for soil remediation [12,8,13]. It has also been shown that poorly crystalline Fe-oxyhydroxy sulfate effectively removes arsenic from soils [14]. While numerous studies have investigated the toxicity of arsenic to rice plants, only a limited number have focused on microorganisms, which play a crucial role as decomposers in the soil ecosystem [15,13,16,17].…”
Section: Introductionmentioning
confidence: 99%